If people’s memories are in danger, is democracy in danger? Reflections on two approaches to research - Lucio-Villegas, Emilio (Adult Education Discourses, 2023)
In this essay, the author reflects on the type of research that it is possible to undertake to produce useful knowledge for common people and, importantly, created by common people starting from their problems, their worries, or their questions. Two different research projects are briefly described, both with an approach based on participatory research. The first, around the repression that occurred in the Spanish Civil War and afterwards during the Franco dictatorship, is research geared to re-appropriate common history and thereby re-write historical memory. The second project has as its focus the re-evaluation of popular craft skills and professions and is centred on examining the significance of the river for a small village in Spain. In the conclusion the author focuses on how this kind of research can help people to leave behind them the Culture of Silence and how it provides them tools for expressing their culture and their histories. The essay also focuses on the co-creation of knowledge as a way to produce alternative knowledge that is able to challenge the official versions of knowledge that stand in contradiction to people’s life experience.